Academic Papers Titles: a Russian - English Perspective - N. K. Riabtseva (Научный диалог, 2018)
The article exposes the cross-cultural incongruence in academic paper titles organization in Russian and in English. The research is based on extensive linguistic corpus data that cover 10 000 paper titles authored by native Russian and English speakers. Its main purpose is to demonstrate that word-for-word translation of paper titles from Russian into English often fails to map standard stylistic patterns characteristic to academic English. It is shown that there is a number of reasons why scientific papers (books, theses, conference reports, etc.) in Russian and in English are titled in different ways. The most important is the difference in the academic style proper in the two languages. While the Russian academic style generates rather extended titles with (multiple) abstract nouns, genitive constructions, etc., incorporated into a single noun group, the English academic style prefers a two-parts title pattern. The latter, in its turn, prefers the and -conjunction, a column, non-finite forms of the verb, prepositions, interrogative constructions, etc. The communicative asymmetry in academic paper titles’ verbalization principles in Russian and in English is no doubt a topical issue for Russian academic community in its way towards effective international cooperation.